FAKTOR â FAKTOR YANG MEMPENGARUHI KUALITAS AUDIT (Studi Empiris Pada Kantor BPKP Perwakilan Provinsi Jawa Tengah) - Gregorius Angga Putama, 14.05.52.0217; Badjuri, Achmad (Students Journal of Accounting and Banking, 2016)
This research aims to determine the factors that affect the quality of the audit ( an empirical study on BPKP Office Representative Of Province in Central Java ). The population in this study are all BPKP auditors who have a certified auditor fuctional positions (JFA) and has experience as an BPKP auditor at least 2 years. Sampling was done by using purposive sampling method and the total sample of 145 respondents. Primary data collection method used is the questionnaire. Data analysis using linear regression. The results showed that motivation, integrity, independencecy, accountability, competence, and profesionalism significant positive effect on audit quality. While the objectivity is not significant positive effect on audit quality. Â Keywords:Â Motivation, Integrity, Objectivity, Independency, Accountability, Competence, Professionalism, Audit Quality